CRIMINALS IDENTIFICATION SYSTEM (CIDS) USING FACE RECOGNITION - Sherif Kamel Hussein & Amal Fahad Almejwal (International Journal of Research Science and Management, 2019)
By evolution of communication technology and face recognition research, many countries start applying face recognition in many places like Airports, Banks, roads...etc. In addition to that, face recognition becomes one of areas that challenged and required by many countries currently to identify criminals via their faces to prevent increasing the rate of crimes. There are many ways that can be obstructed by humans to avoid this recognition like wearing colored contact lenses, growing a mustache, putting on intense make-up...etc. In this paper the authors introduce new system that depends on face identification and image processing to identify criminals from their faces even after a long time. It is designed to facilitate managing a criminal identification by making admins more able to Add a criminal to database, update their information and deleting them from the database, Check criminal records and Add cops to the database... etc